Prevalence of Tuberculosis and Human Immunodeficiency Virus Co-infection and Associated Factors among People Living With Human Immunodeficiency Virus at Burayu and Holeta Districts, Oromia Region, Ethiopia - Duressa, Desalegn; Sorsa, Solomon; Asnake, Solomon (Journal of Science and Development, 2018)
Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) are the double burden diseases of the world. The African continent takes a great share of TB-HIV cases worldwide. This retrospective study was conducted to assess the prevalence of TB-HIV co-infection and associated factors in Burayu and Holeta health centers. A ten years retrospective study was conducted by reviewing files of HIV/AIDS patients attending HIV clinics in the two health centers (2008-2017). Data were coded, cleaned and analyzed using SPSS version 20 statistical software. A P-value <0.05 was considered statistically significant. Among 2937 people living with HIV/AIDS, 13.3% (95% CI: 12.07-14.53) were TB-HIV co-infected, the majority were males and in the age group of 15-45years. CD4+ cell count <200cells/mm3 (χ2 = 58.22 P<0.001), WHO clinical stage III and IV (χ2 = 119.3; P<0.001), antiretroviral drug adherence (χ2 = 92.31; P< 0.001) nutritional status (χ2 = 89.4; P < 0.001) were significantly associated with HIV-TB co-infection. The prevalence of TB among HIV patients at two health centers was moderately high. Therefore, TB screening among HIV-positive patients is mandatory. In addition, community mobilization on early case detection and health education on TB-HIV co-infection should be encouraged.